Defects at play: Shaping the photophysics and photochemistry of ice - Marta Monti; Yu Jin; Gonzalo Díaz Mirón; Arpan Kundu; Marco Govoni; Giulia Galli; Ali Hassanali (Proceedings of the National Academy of Sciences, 2025)
The mechanisms by which light interacts with ice and the impact of photoinduced reactions are central to our understanding of environmental, atmospheric, and astrophysical processes. However, a microscopic description of the photoproducts originating from ultraviolet (UV) absorption and emission processes has remained elusive. Here, we explore the photochemistry of ice using time-dependent hybrid density functional theory on various models of pristine and defective ice Ih. Our investigation of the excited state potential energy surface of the crystal shows that UV absorption can lead to the formation of hydronium ions, hydroxyl radicals, and excess electrons. One of the dominant mechanisms of decay from the excited to the ground-state involves the recombination of the electron with the hydroxyl radical yielding hydronium-hydroxide ion-pairs. We find that the details of this charge recombination process sensitively depend on the presence of defects in the lattice, such as vacancies and preexisting photoproducts. We also observe the formation of Bjerrum defects following UV absorption; we suggest that, together with hydroxide anions, they are likely responsible for prominent features experimentally detected in long UV exposure absorption spectra, remarkably red-shifted relative to short exposure spectra. Our results highlight the key role of defects in determining the onset of absorption and emission processes in ice.